2002
DOI: 10.1124/jpet.102.038570
|View full text |Cite
|
Sign up to set email alerts
|

The Sea Anemone Toxins BgII and BgIII Prolong the Inactivation Time Course of the Tetrodotoxin-Sensitive Sodium Current in Rat Dorsal Root Ganglion Neurons

Abstract: We have characterized the effects of BgII and BgIII, two sea anemone peptides with almost identical sequences (they only differ by a single amino acid), on neuronal sodium currents using the whole-cell patch-clamp technique. Neurons of dorsal root ganglia of Wistar rats (P5-9) in primary culture (LeibovitzЈs L15 medium; 37°C, 95% air/5% CO 2 ) were used for this study (n ϭ 154). These cells express two sodium current subtypes: tetrodotoxin-sensitive (TTX-S; K i ϭ 0.3 nM) and tetrodotoxinresistant (TTX-R; K i ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…This result was consistent with the site-3 toxin (Salceda et al 2002(Salceda et al , 2006Benzinger et al 1997). For example, the sea anemone toxins BgII and BgIII prolong the inactivation time course of the tetrodotoxin-sensitive sodium current in dorsal root ganglion neurons.…”
Section: Inactivationsupporting
confidence: 86%
“…This result was consistent with the site-3 toxin (Salceda et al 2002(Salceda et al , 2006Benzinger et al 1997). For example, the sea anemone toxins BgII and BgIII prolong the inactivation time course of the tetrodotoxin-sensitive sodium current in dorsal root ganglion neurons.…”
Section: Inactivationsupporting
confidence: 86%
“…The use of this and other toxins that prolong Na ϩ -channel inactivation such as BgII and BgIII (the toxins isolated from the sea anemone Bunodosoma granulifera; Bosmans et al 2002;Salceda et al 2002) and CgNa (the toxin isolated from the sea anemone Condylactis gigantea; Billen et al 2010;Ständker et al 2006) would further support the functional coupling between K Na channels and voltage-dependent persistent Na ϩ current in cricket Kenyon cells. Hage and Salkoff (2012) suggested that I Naf is not responsible for the activation of K Na channels because I KNa persists even when I Naf is eliminated or reduced by a depolarizing holding potential of Ϫ50 mV in tufted/mitral cells.…”
Section: Discussionmentioning
confidence: 99%
“…21c). This high dose was used, because the TTX sensitivities of the voltagedependent sodium channels were different (Salceda et al 2002;Djouhri et al 2003); some types of channels (e.g. Na v 1.7 channels) required high concentrations of TTX to block their conduction, whereas others were resistant to TTX.…”
Section: Monoamine Concentrations In the Body Wallmentioning
confidence: 99%